Evaluation the learning styles of dental students of Mazandaran University of Medical Sciences - Anahita Ghorbani; Mahmood Moosazadeh; Mohammad Ghaemi; Maryam Zamanzadeh (Mashhad University of Medical Sciences, 2023)
Background: Knowledge of students' learning styles can facilitate changing teaching methods according to their learning styles and subsequently improve their educational performance. Accordingly, this study aimed to investigate the learning styles of dental students at Mazandaran University of Medical Sciences. Method: This cross-sectional descriptive study was conducted in 2020 on 184 dental students at Mazandaran University of Medical Sciences. The dental students at the 5th semester and higher academic levels were selected through the census method, and the data were collected using the VARK Learning Styles Self-Assessment Questionnaire. This is a standard 16-item multiple-choice assessment that identifies preferred learning styles: visual (V), auditory (A), reading/writing (R), and kinesthetic (K). The collected data were analyzed with SPSS V.24  and using descriptive statistics (mean, standard deviation, etc.) and inferential statistics (independent samples t-test). Results: 184 students including 94 men (51%) and 90 women (49%) with an average age of 22.7 years participated in this study. The results showed that the students at Sari Dental School follow different learning styles, and the aural style (37.5%) was the most frequently preferred style for them. However, a significant difference was found between male and female students in terms of their preferred learning styles (p=0.608). Conclusion: Improving the quality of education requires taking learning styles in the teaching profession and educational tools into account. Teachers' knowledge of the types of learning styles and choosing the style that is most consistent with students' learning styles can significantly improve the efficiency of educational courses.